SIFAT FISIKOKIMIA DAN ORGANOLEPTIK FLAKE BERAS MERAH DENGAN VARIASI SUHU PEREBUSAN DAN SUHU PENGERINGAN - Chandra, Lily; Marsono, Yustinus; Sutedja, Anita Maya (Widya Mandala Surabaya Catholic University, 2014)
Flake is one of a high starch content that might increase the consumption of red rice. Important process are carried out to obtain the desired product of flake is boiling and drying. Variations in boiling and drying temperature affect the characteristics of the desired product. The research design used was randomized block design (RAK) factorial with two factors, the boiling temperature consists of 3 (three) standard treatment R1 (70°C), R2 (80°C), R3 (90°C) and the drying temperature consists of 3 (three) standard treatment K1 (50°C), K2 (60°C), K3 (70°C). Each treatment was repeated 2 times. The parameters tested is moisture content, rehydration, color, hardness, the size and shape of starch granules, organoleptic test (starchy flavor, mouthfeel, flavor with milk) and ash content, protein content, fat content for the best treatment. The data then analyzed using ANOVA at α = 5% to determine whether there is a marked influence on the parameters of the study. If there is a real effect, then continued with DMRT analysis. Drying temperature gave the different to the moisture content of red rice flake. Boiling temperature gave the different to hardness, rehydration, lightness, yellowness, the size and shape of starch granules red rice flake. Variations of boiling and drying temperature resulted in a different in flavor, starchy flavor, and mouthfeel of red rice flake. The best treatment was boiling temperature 80°C and drying temperature 70°C. The product has 5,35% moisture content, 170,06 N hardness, 198,37% rehydration, 48,90 lightness, 16,45 redness, 13,75 yellowness, and sensory evaluation values was 5,60; 5,12 and 5,55 for flavor, starchy flavor, and mouthfeel, respectively.